2008
DOI: 10.1101/sqb.2008.73.021
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of Neural Progenitor Cells: A Novel Approach to Biomarker Discovery

Abstract: Finding biomarkers of human neurological diseases is one of the most pressing goals of modern medicine. Most neurological disorders are recognized too late because of the lack of biomarkers that can identify early pathological processes in the living brain. Late diagnosis leads to late therapy and poor prognosis. Therefore, during the past decade, a major endeavor of clinical investigations in neurology has been the search for diagnostic and prognostic biomarkers of brain disease. Recently, a new field of meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 87 publications
0
20
0
Order By: Relevance
“…Since previous studies have demonstrated a possible association of mobile lipids with apoptosis, 4244 neuronal loss, and/or neuronal stem cell generation, 45,46 we were also interested in exploring whether there were changes in mobile lipids resonating at ≈1.30ppm and/or 0.9ppm in the sevoflurane-exposed rat pups. The spectral signature at 1.30ppm (represented by [Lip13a]) showed that there was a trend towards increase in the exposed group, particularly on PND8; however, this difference was not statistically significant (p>0.05, results not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Since previous studies have demonstrated a possible association of mobile lipids with apoptosis, 4244 neuronal loss, and/or neuronal stem cell generation, 45,46 we were also interested in exploring whether there were changes in mobile lipids resonating at ≈1.30ppm and/or 0.9ppm in the sevoflurane-exposed rat pups. The spectral signature at 1.30ppm (represented by [Lip13a]) showed that there was a trend towards increase in the exposed group, particularly on PND8; however, this difference was not statistically significant (p>0.05, results not shown).…”
Section: Resultsmentioning
confidence: 99%
“…It is becoming increasingly clear, from work in our (18,21,37) and others' (20,24,27,28,46) laboratories, that metabolomics possesses significant as yet untapped potential for biomarker discovery, since it represents the signature of the actual processes that are occurring within the body rather than compounds (such as untranscribed DNA or pre-or posttranslationally modified proteins) that may be superfluous to these processes. In addition, there are a relatively small number of metabolites to examine compared with genes, transcripts, and proteins in their respective "omics" fields.…”
mentioning
confidence: 99%
“…By using proton magnetic resonance spectroscopy, Maletić-Savatić et al discovered a metabolic biomarker of NSCs for the analysis in the live human brain, which connected systems with cellular neurobiology through the uses of certain specific metabolites. Thus, they give a functional observation into the living human brain, which may pave the way to the eventual discoveries of useful biomarkers of the diseases in clinic [75]. …”
Section: Bioinformatics Methods For Analyzing the Novel Therapeutimentioning
confidence: 99%